A diabetes specialist nurse audit within NHS England. (7th October 2020) - Hicks, Debbie; James, June
Abstract: The diabetes specialist nurse (DSN) works wholly in diabetes care and plays an integral part in diabetes multidisciplinary teams; the benefits of the role are well recognised. The post emerged in the 1950s and it was designed to support both people living with diabetes and health care professionals not working in specialist teams. Previous audits of DSNs indicated that the numbers of nurses working in this role were reducing and concerns were raised at national level about how this might impact on the care of an ever expanding population with diabetes. This audit through a 'Freedom of Information' request has identified many more DSNs than previous audits. It has also demonstrated a plethora of different job titles, whether most were employed in hospital or in primary care, and their banding. This audit has prompted the need for other information gathering and investigation which will aid workforce development. Copyright © 2020 John Wiley & Sons.